Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
प्रश्न में, बिंदु \((2,3)\) दोनों रैखिक समीकरणों के आलेखों पर स्थित है। पहले समीकरण को देखते हैं:
[tex]\[ 3x - (a-1)y = 2a - 1 \][/tex]
बिंदु \((2, 3)\) को इस समीकरण में प्रतिस्थापित करते हैं:
[tex]\[ 3(2) - (a-1)(3) = 2a - 1 \][/tex]
इसको सुलझाते हैं:
[tex]\[ 6 - 3(a - 1) = 2a - 1 \][/tex]
अंदर के ब्रैकेट्स को खोलते हैं:
[tex]\[ 6 - 3a + 3 = 2a - 1 \][/tex]
इसे फिर से व्यवस्थित करते हैं:
[tex]\[ 9 - 3a = 2a - 1 \][/tex]
सभी \(a\) को एक तरफ और सभी स्थिरांक को दूसरी तरफ रखते हैं:
[tex]\[ 9 + 1 = 2a + 3a \][/tex]
[tex]\[ 10 = 5a \][/tex]
[tex]\[ a = 2 \][/tex]
अब इस \(a\) के मान को दूसरे समीकरण में प्रतिस्थापित करते हैं:
[tex]\[ 5x + (1 - 2a)y = 3b \][/tex]
बिंदु \((2, 3)\) को इस समीकरण में प्रतिस्थापित करते हैं और \(a = 2\) को उपयोग करते हैं:
[tex]\[ 5(2) + (1 - 2(2))(3) = 3b \][/tex]
इसको सुलझाते हैं:
[tex]\[ 10 + (1 - 4)(3) = 3b \][/tex]
[tex]\[ 10 + (-3)(3) = 3b \][/tex]
[tex]\[ 10 - 9 = 3b \][/tex]
[tex]\[ 1 = 3b \][/tex]
[tex]\[ b = \frac{1}{3} \][/tex]
तो, [tex]\(b\)[/tex] का मान [tex]\(\frac{1}{3}\)[/tex] है।
[tex]\[ 3x - (a-1)y = 2a - 1 \][/tex]
बिंदु \((2, 3)\) को इस समीकरण में प्रतिस्थापित करते हैं:
[tex]\[ 3(2) - (a-1)(3) = 2a - 1 \][/tex]
इसको सुलझाते हैं:
[tex]\[ 6 - 3(a - 1) = 2a - 1 \][/tex]
अंदर के ब्रैकेट्स को खोलते हैं:
[tex]\[ 6 - 3a + 3 = 2a - 1 \][/tex]
इसे फिर से व्यवस्थित करते हैं:
[tex]\[ 9 - 3a = 2a - 1 \][/tex]
सभी \(a\) को एक तरफ और सभी स्थिरांक को दूसरी तरफ रखते हैं:
[tex]\[ 9 + 1 = 2a + 3a \][/tex]
[tex]\[ 10 = 5a \][/tex]
[tex]\[ a = 2 \][/tex]
अब इस \(a\) के मान को दूसरे समीकरण में प्रतिस्थापित करते हैं:
[tex]\[ 5x + (1 - 2a)y = 3b \][/tex]
बिंदु \((2, 3)\) को इस समीकरण में प्रतिस्थापित करते हैं और \(a = 2\) को उपयोग करते हैं:
[tex]\[ 5(2) + (1 - 2(2))(3) = 3b \][/tex]
इसको सुलझाते हैं:
[tex]\[ 10 + (1 - 4)(3) = 3b \][/tex]
[tex]\[ 10 + (-3)(3) = 3b \][/tex]
[tex]\[ 10 - 9 = 3b \][/tex]
[tex]\[ 1 = 3b \][/tex]
[tex]\[ b = \frac{1}{3} \][/tex]
तो, [tex]\(b\)[/tex] का मान [tex]\(\frac{1}{3}\)[/tex] है।
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.